Lexical lists and the birth of a lexicographer: the case of Vincenzo Monti (Prassi Ecdotiche della Modernità Letteraria, 2018)
The lexical lists that can be found in the avantext of the Proposta di alcune correzioni ed aggiunte al Vocabolario della Crusca (1817-1826) by Vincenzo Monti allow to highlight some of the mechanisms which set the making of the poet’s lexicographic and linguistic thought from an unprecedented point of view.
Keywords: Lexical lists; lexicography; philology; history of linguistic thought